The new division of labour : emerging forms of work organisation in international perspective - Littek, W. (Wolfgang), 1937-; Charles, Tony, 1946- (De Gruyter studies in organization ;, 1995)
The New Division of Labor: Emerging Forms of Work Organization in International Perspective.